Atlas of Pelvic Floor Ultrasound - Dietz, Hans Peter; Hoyte, Lennox P.J.; Steensma, Anneke B.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2008)
Ultrasound has replaced X-ray as the main imaging modality for the diagnosis of pelvic floor disorders in the female. Most recent developments - volume contrast, speckle reduction and multi-slice imaging - have markedly enhanced spatial resolution and ease of use, with the result that ultrasound now enables cost-effective and non-invasive demonstration of bladder neck and pelvic organ mobility, vaginal, urethral and levator ani function and anatomy, and anorectal anatomy. Atlas of Pelvic Floor Ultrasound provides an introduction to pelvic floor imaging, as well as a resource to be used during initial and more advanced practice. This atlas is an invaluable resource for gynecologists, urogynecologists, female urologists, sonologists, radiologists, and physiotherapists.
Live Anatomy of the Pelvic Floor: An MRI Perspective -- Pelvic Floor Ultrasound: Basic Physics, Instrumentation, and Examination Technique -- 3D/4D Imaging: Technical Overview and Basic Methodology -- The Anterior Compartment -- The Central and Posterior Compartments -- Axial Plane Imaging -- Imaging of Implant Materials -- Outlook -- An Introduction to 4D View™ (Version 5.0).
Keywords: Radiology; Urology; Gynecology .; Imaging / Radiology; Ultrasound; Urology; Gynecology